Influencer Quality in Promoting Perspectives Products - Mita Fransiska; Irmawan Rahyadi; Olivia Priskha Dewi; Almira Danella Azzahra; Dhea Amelia Irawan (Syntax Idea)
Influencers holds an important role in product marketing due to the growth of internet and social media users in Indonesia as well as the increasing economic value of the e-commerce sector and has become an effective strategy in influencing consumer behaviour. A thematic analysis approach was used to identify key themes from literature searches in scientific databases like Wiley, Taylor & Francis, Sage, and Elsevier, on English articles from 2020 to 2023, addressing influencer collaborations with brands. Findings showed influencer quality, factors like credibility, personality, compatibility between influencer and product, and interaction with followers, contribute to promotional effectiveness. Use of language, emotional aspects and interaction also have a significant impact on audience engagement. The influencer's previous testimonials provide a deeper understanding of the product usage